The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.13075/ijomeh.1896.01195
|View full text |Cite
|
Sign up to set email alerts
|

Environmental exposure to non-persistent endocrine disrupting chemicals and semen quality: An overview of the current epidemiological evidence

Abstract: Some of the recent publications have reported a decline in semen quality in the last few decades. This phenomenon is associated with environmental factors, particularly with exposure to endocrine disrupting chemicals (EDCs). The aim of this publication is to critically review the literature on exposure to the following 6 ubiquitous environmental non-persistent EDCs: bisphenol A, triclosan, parabens, synthetic pyrethroids, organophosphate pesticides and phthalates, and on their influence on semen quality measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 105 publications
0
47
0
1
Order By: Relevance
“…Their application ranges from food packaging materials to their use in medical devices. Epidemiological studies have shown that exposure to several phthalates are linked to impaired male reproductive function and semen quality [90,91].…”
Section: Phthalatesmentioning
confidence: 99%
“…Their application ranges from food packaging materials to their use in medical devices. Epidemiological studies have shown that exposure to several phthalates are linked to impaired male reproductive function and semen quality [90,91].…”
Section: Phthalatesmentioning
confidence: 99%
“…The National Institute of Environmental Health Sciences defines EDCs as "chemicals that interfere with the body's endocrine system and produce adverse developmental, reproductive, neurological and immune effects." Phthalates are broadly classified as endocrine disruptors in wildlife and human Lyche et al, 2009;Su et al, 2014;Bansal et al 2018;Zamkowska et al, 2018). In humans, phthalate exposure alters steroid levels during gestation, infancy, and adulthood Lyche et al, 2009;Su et al, 2014).…”
Section: Suggested Effects Of Phthalates On Health As Endocrine Disrumentioning
confidence: 99%
“…5 Several factors in adult life have been linked to reduced semen quality, including lifestyle such as smoking, chronic alcohol use, obesity, sleep, and nutrition [6][7][8][9][10][11][12] and occupational and environmental exposures such as sedentary work, radiation, air pollution, bisphenol A, parabens, organophosphate pesticides, pyrethroids, and phthalates. [13][14][15][16][17] Still, subfertility remains unexplained for many, and the underlying causes are far from understood. According to the 'fetal origins of adult disease hypothesis' suggested by Barker and Osmond in 1986, the environment encountered during fetal life is strongly related to the risk of developing non-communicable diseases later in life.…”
Section: Introductionmentioning
confidence: 99%